The Influence of Earnings Quality, Banking Technology, Operational Efficiency, and Non-Performing Loans (NPL) on Firm Value - Albi, Rachma Utari; Komalasari, Agrianti; Syaipudin, Usep (Jurnal Economic Resource, 2025)
This study examines the influence of earnings quality, banking technology, operational efficiency, and non-performing loans (NPLs) on firm value in the Indonesian banking sector. Employing a quantitative approach, the study analyzes secondary data from conventional banks listed on the Indonesia Stock Exchange (IDX) between 2021 and 2023. Tobin’s Q is used to measure firm value, while independent variables include Net Profit Margin (NPM), mobile banking usage, BOPO (operating expenses to income ratio), and NPLs. The results reveal that earnings quality (NPM) and banking technology (mobile banking) have a significant positive effect on firm value, indicating that profitability and digital adoption enhance investor trust and market valuation. Conversely, operational inefficiency (BOPO) and high NPL levels negatively impact firm value, suggesting that cost control and credit risk management are critical to sustaining financial performance. Firm size also demonstrates a significant positive effect, underscoring its role in reinforcing stability and resilience in dynamic financial environments. This research contributes to the understanding of how financial and technological variables interact to shape firm value, particularly amid the digital transformation of the banking industry. The findings support both signaling and stakeholder theories, indicating that transparent, efficient, and tech-savvy operations serve as credible signals to investors and promote long-term value creation.